Faktor-Faktor Penyebab Kesulitan Belajar Matematika pada Siswa Kelas IV Sekolah Dasar - Hamidah, Nur; Ain, Siti Quratul (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2022)
This study aims to determine the factors that cause learning difficulties in mathematics experienced by fourth-grade elementary school students. This type of research is descriptive qualitative. The data sources in this study were fourth-grade teachers and all fourth-grade students at SD Negeri 09 Maredan which consisted of 24 students. Data collection techniques in this study were observation, interviews, and documentation with 3 stages, namely data reduction, data presentation, and conclusion drawing. The data analysis technique used the Miles and Huberman model. The results showed that the factors causing student difficulties can be seen from two factors, namely internal factors, and external factors. Internal factors are student interest and enthusiasm in learning, student readiness in the learning process, student intelligence, student body, and mental condition, study habits, student interest in mathematics. While the external factors of students' difficulties in mathematics lessons in grade IV elementary school are: environmental conditions of students, parents' attention to the learning process, relationships with parents and those around them, relationships with teachers and friends at school, media and teaching materials as supporting tools in the school. class during the learning process, the condition of the classroom and school environment, the difficulty of the material in the content of mathematics lessons. The teacher's efforts to overcome the learning difficulties of fourth-grade elementary school students are increasing students' lack of interest and enthusiasm for learning, providing special guidance to students, adding media and teaching materials as supporting tools in the classroom.